Does COVID-19 threat increase xenophobia? The roles of protection efficacy and support seeking - Zhuang She; Ningning Zhou; Dan Li; Shengtao Ren; Weidong Ji; Juzhe Xi (BMC, 2022)
Abstract Background In response to the COVID-19 pandemic, people in many countries have shown xenophobia toward China, where the pandemic began. Within China, xenophobia has also been observed toward the people of Wuhan, the city where the first cases were identified. The relationship between disease threat and xenophobia is well established, but the reasons for this relationship are unclear. This study investigated the mediation role of perceived protection efficacy and moderation role of support seeking in the relationship between perceived COVID-19 risk and xenophobia within China. Methods An online survey was administered to a nationally representative sample (N = 1103; 51.7% women; ages 18 to 88) of Chinese adults during the early stage of the COVID-19 pandemic. Participants completed questionnaires about their perceived COVID-19 risk, perceived protection efficacy in reducing risk, support seeking, and xenophobic attitudes toward people of the Wuhan area. Results Regression based analyses showed that the perceived COVID-19 risk positively predicted xenophobia. Low perceived protection efficacy partly mediated the relationship between perceived COVID-19 risk and xenophobic attitudes, and this indirect effect was moderated by support seeking. Specifically, the indirect effect was weaker among individuals who sought more social support. Conclusions Under disease threat, xenophobia can appear within a country that otherwise seems culturally homogeneous. This study extends the extant research by identifying a possible psychological mechanism by which individuals' perception of disease threat elicits xenophobia, and by addressing the question of why this response is stronger among some people than others. Increasing the public's perceived efficacy in protecting themselves from infection, and encouraging support seeking, could reduce xenophobic attitudes.